IELTS to success preparation tips and practice tests = Hướng dẫn cách luyện thi và các bài thi thực hành - Bemmel, Eric van. (Nxb Tp.HCM, 2000)
IELTS to success is designed to help you prepare for the IELTS examination by providing strategies and material for practice in all areas of the test. This book is aimed specifically at people talking the IELTS Academic Module rather than the general tranning module.